2019
DOI: 10.3389/fpls.2019.00914
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-Dependent Cell Elongation During the Shade Avoidance Response

Abstract: Plant uses multiple photoreceptors and downstream components to rapidly respond to dynamic changes in environmental light. Under shade conditions, many species exhibit shade avoidance responses that promote stem and petiole elongation, thus helping plants reach the sunlight. In the last few years, the regulatory molecular mechanisms by which plants respond to shade signals have been intensively studied. This review discusses the regulatory mechanisms underlying auxin-mediated cell elongation in the shade avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 85 publications
3
62
0
Order By: Relevance
“…A study of elongation of the hypocotyl in Arabidopsis under shade shows that cotyledon-derived auxin is necessary to initiate hypocotyl growth [23]. In our study, elongation was associated with an increase in auxin levels in leaves, which suggests that shade induces a crosstalk within hormones [44] and the auxin promotes elongation under shade [49]. Our analysis of gene regulation in multiple plant hormone signal pathways revealed that the growth promoting hormones auxin, gibberellin, brassinosteroid, cytokinine and senescing hormones of abscisic acid and ethylene were all stimulated under shade treatment.…”
Section: Discussionsupporting
confidence: 55%
“…A study of elongation of the hypocotyl in Arabidopsis under shade shows that cotyledon-derived auxin is necessary to initiate hypocotyl growth [23]. In our study, elongation was associated with an increase in auxin levels in leaves, which suggests that shade induces a crosstalk within hormones [44] and the auxin promotes elongation under shade [49]. Our analysis of gene regulation in multiple plant hormone signal pathways revealed that the growth promoting hormones auxin, gibberellin, brassinosteroid, cytokinine and senescing hormones of abscisic acid and ethylene were all stimulated under shade treatment.…”
Section: Discussionsupporting
confidence: 55%
“…Other genes regulating shade avoidance responses at the organ and whole plant levels are also overexpressed in purple basil. This is the case with AUXIN RESPONSE 4 (AXR4), an activator of the Auxin Influx Carrier Protein 1 (AUX1, Dharmasiri et al, 2006), that induces hypocotyl elongation (Ma & Li, 2019), and of BYPASS 1 (BPS1), whose overexpression promotes both apical dominance and leaf expansion (Lee, Parrott, Adhikari, Fraser, & Sieburth, 2016). It is also true of LONGIFOLIA 1, LONGIFOLIA 2 and a set of EXPANSINs (EXP 1,4,8,10), all of which are known to be involved in shade avoidance responses (Christie, 2007;Sasidharan, Chinnappa, Voesenek, & Pierik, 2008 (Hu, Xie, & Chua, 2003;.…”
Section: Dissecting Molecular Events At the Base Of The Shade Naturmentioning
confidence: 99%
“…In the past decade, shade related research was carried out mainly in Arabidopsis , and indicated a crucial role of auxin in the shade avoidance response ( Sessa et al, 2018 ). In the Arabidopsis seedlings, auxin accumulates in response to shade resulting in hypocotyl cells elongation ( Ma and Li, 2019 ). A low R:FR ratio (as in case of shade) has been found to promote petiole elongation in Arabidopsis ( Roig-Villanova and Martínez-García, 2016 ).…”
Section: Hormonal Regulation Of Plant Development In Darkmentioning
confidence: 99%